A Rare Case of the Digenic Inheritance of Long QT Syndrome Type 2 and Type 6 - Annejet Heida; Lisette J. M. E. van der Does; Ahmed A. Y. Ragab; Natasja M. S. de Groot (Case Reports in Medicine)
We report a 37-year-old woman with an out-of-hospital cardiac arrest caused by ventricular fibrillation due to digenic inheritance of long QT syndrome type 2 (KCNH2 gene) and type 6 (KCNE2 gene). During hospitalization, prolonged QTc intervals and frequent episodes of ventricular tachyarrhythmias manifested. Genetic testing identified a mutation of the KCNH2 gene and an unclassified variant, most likely pathogenic, of the KCNE2 gene. This digenic inheritance is extremely rare.